Discovery of benzochalcone derivative as a potential antigastric cancer agent targeting signal transducer and activator of transcription 3 (STAT3) - Jinyun Dong; Jing Yang; Wenkai Yu; Haobin Li; Maohua Cai; Jing-Li Xu; Han-Dong Xu; Yun-Fu Shi; Xiaoqing Guan; Xiang‑Dong Cheng; Jiang‑Jiang Qin (Taylor & Francis Group, 2022)
Gastric cancer remains a significant health burden worldwide. In continuation of our previous study and development of effective small molecules against gastric cancer, a series of benzochalcone analogues involving heterocyclic molecules were synthesised and biologically evaluated in vitro and in vivo. Among them, the quinolin-6-yl substituted derivative KL-6 inhibited the growth of gastric cancer cells (HGC27, MKN28, AZ521, AGS, and MKN1) with a submicromolar to micromolar range of IC50, being the most potent one in this series. Additionally, KL-6 significantly inhibited the colony formation, migration and invasion, and effectively induced apoptosis of MKN1 cells in a concentration-dependent manner. The mechanistic study revealed that KL-6 could concentration-dependently suppress STAT3 phosphorylation, which may partly contribute to its anticancer activity. Furthermore, in vivo antitumour study on the MKN1 orthotopic tumour model showed that KL-6 effectively inhibited tumour growth (TGI of 78%) and metastasis without obvious toxicity. Collectively, compound KL-6 may support the further development of candidates for gastric cancer treatment.